Do the various sources of energy consumption affect the environmental degradation in India? - Bin Mohamad, Abdul Hayy Haziq; Ab-Rahim, Rossazana (International Journal of Renewable Energy Development, 2024)
India possesses ample opportunities for economic growth, resulting in a surge in electricity demand. As per the Environmental Performance Index (EPI), India's rank on environmental health and ecosystem viability stands at a lowly 168th out of 180 countries. Historically, India relied on fossil fuels for electricity generation, leading to substantial environmental degradation that have harmed the environment. In recent times, India has diversified its electricity generation sources, incorporating not only fossil fuels but also nuclear power and renewable resources. However, despite these changes, India still struggles with high CO2 emissions which indicates the level of environmental degradation. Hence, this study aims to investigate the sources of energy consumption in India: fossil fuels, renewable energy, and nuclear energy. By utilising the ARDL and NARDL methodologies, this study enriches the empirical studies by examining energy consumption trends in India from 1985 to 2021. The findings of this study shed light on whether the adoption of renewable energy and nuclear energy significantly aids in reducing carbon emissions in India, thereby facilitating the attainment of the Sustainable Development Goal (SDG), Therefore, it is of the utmost necessity for India to emphasize the formation of clean energy in their energy policy to achieve the SDG7 by the year 2030. This study found a positive correlation between GDP per capita and CO2 emissions, highlighting the urgent need to reduce India's dependency on fossil fuels. The ARDL analysis further confirms that fossil fuel-generated energy contributes to CO2 emissions, whereas nuclear-generated energy reduces them.